Activation of human immunodeficiency virus type 1 in monocytoid cells by the protozoan parasite Leishmania donovani. - Bernier, R (1995)
In this study, we demonstrated that the protozoan parasite Leishmania donovani and one of its major surface molecules, the lipophosphoglycan (LPG), can induce human immunodeficiency virus type 1 (HIV-1) expression in U1 and OM-10.1, two cell lines of monocytoid origin latently infected with HIV-1. Treatment of U1 cells with various concentrations of LPG (1, 5, and 10 microM) resulted in a dose-dependent secretion of tumor necrosis factor alpha (TNF-alpha). Suppression of LPG-induced HIV-1 expression by polyclonal anti-TNF-alpha antibodies further confirmed the involvement of this cytokine. Results from these studies indicate that the protozoan parasite L. donovani can induce the secretion of TNF-alpha that will function in an autocrine or paracrine manner to upregulate HIV-1 expression. Our data suggest for the first time that this protozoan parasite can be viewed as a potential cofactor in the pathogenesis of AIDS.